2D Boron Nanoplatelets as a Multifunctional Additive for Osteogenic, Gram-Negative Antimicrobial and Mechanically Reinforcing Bone Repair Scaffolds - Coleman, Jonathan; Prendeville, Lucy; Carey, Tian (My University, 2025)
Two-dimensional boron offers unique advantages in bone tissue engineering, unlocking capabilities that conventional additives struggle to achieve. Herein, the 2D morphology and intrinsic bioactivity of boron nanoplatelets are leveraged, to be incorporated into collagen-based scaffolds and simultaneously achieve osteogenic, mechanically reinforcing, and antimicrobial effects, with a shift toward neurogenic, angiogenic, and anti-inflammatory signaling. Boron nanoplatelets, synthesized from nonlayered precursors using liquid-phase exfoliation, are combined with collagen to form boron-collagen scaffolds (BColl). Boron significantly reinforces the collagen matrix, beneficial for mechanoresponsive bone cells. Osteoblasts and mesenchymal stem cells exhibit healthy morphology and proliferation on BColl films and scaffolds, with extended culture leading to increased alkaline phosphatase release and significantly increased calcium deposition, indicating enhanced osteogenesis. E. coli viability decreases significantly on BColl films, demonstrating their potential to limit postimplantation infections. Finally, angiogenic, neurogenic, and anti-inflammatory signaling, with dose-dependent upregulation of vascular endothelial growth factor-A, nerve growth factor-beta, and interleukin-10, and downregulation of interleukin-6 are observed, highlighting boron's potential to drive pro-reparative processes. Taken together, these data showcase boron's potential for next-generation bone biomaterials, by offering multifunctional benefits to clinically relevant aspects of bone regeneration such as mineralization, angiogenesis, and innervation, while improving the mechanical and antimicrobial properties of natural polymer scaffolds.
PUBLISHED
Cited by: 0; All Open Access; Gold Open Access; Green Accepted Open Access; Green Open Access
Keywords: boron-collagen scaffolds (BColl); Boron nanoplatelets; boron-collagen scaffolds (BColl); Boron nanoplatelets